Concept of “baku masuk” as a harmonious Cultural symbol in ambon - Nurlaila Tuanany (12 Waiheru, 2022)
This paper aims to describe how the dominant culture of the Ambonese can be used as a symbol of harmony in cultural plurality and ethnic pluralism in Ambon City. The cultural plurality that has been segregated through knowledge of territorial and geographical boundaries as a differentiator can be overcome through the "Baku Masuk" culture where ethnic diversity in Ambon City can borrow from each other as a form of willingness to accept differences and at the same time be united in differences and henceforth made into as the public culture of every ethnic entity in Ambon City. This paper has found that the “Baku Masuk” culture which is practiced in Ambon City has become a solution for a harmonious life. This paper recommends the need for local culture as a basis for strengthening public culture to be practiced in a plural society.